Crucifixion of masculinity : a gender critical (re)reading of the narrative of the cross as portrayed in the Gospel of Luke - Muller van Velden, Nina Elisabeth (Stellenbosch : Stellenbosch University, 2014)
Thesis (MTh)--Stellenbosch University, 2014.